10 CFR 50.46c Rulemaking: A Novel Approach in Restating the LOCA Problem for PWRs. (1st November 2016) - Frepoli, Cesare; Yurko, Joseph P.; Szilard, Ronaldo H.; Smith, Curtis L.; Youngblood, Robert; Zhang, Hongbin
Abstract: The U.S. Nuclear Regulatory Commission (NRC) is considering a rulemaking that would revise requirements in 10 CFR 50.46 [also known as the emergency core cooling system (ECCS) rule]. Experimental work sponsored by the NRC suggested that the current regulatory acceptance criteria on ECCS performance during design-basis accidents are actually nonconservative for higher-burnup fuel, that embrittlement mechanisms not contemplated in the original criteria exist, and that the 17% limit on oxidation is not adequate to preserve the level of ductility that the NRC originally deemed to be warranted for adequate protection. The new rule imposes new acceptance criteria and is expected to be in effect within this decade. An implementation plan was developed that will give individual plants up to 7 years with which to comply once the rule is amended, depending on the status of each plant's analysis of record, the effort involved, and existing analytical margin to the limits. The proposed rule may challenge U.S. light water reactor fleet operational flexibility and economics. Within the U.S. Department of Energy Light Water Reactor Sustainability Program, the Idaho National Laboratory is pursuing an initiative that is focused on industry applications using Risk-Informed Safety Margin Characterization (RISMC) tools and methods applied to issues that are of current interest to the operating fleet. The mission of RISMC is to provide cost-beneficial approaches to safety analysis by leveraging modern methods, augmented tools (a combination of existing and new), and repurposed data (existing, but used in a new way).